Necrotizing fasciitis caused by Pseudomonas aeruginosa: a rare case report and recent concepts in diagnosis and management - Kumar, Naresh; Lamba, Akshay; Das, Jyotirmay; Neogi, Avik K.; Arora, Kunal; Jaiswal, Surinder; Jain, Mayank; Chhabra, Sargam; Sharma, Urvashi; Malik, Navdeep (International Journal of Research in Orthopaedics, 2020)
Necrotizing fasciitis caused by Pseudomonas aeruginosa is an extremely rare and life threatening bacterial soft tissue infection. Here we report a case study of fully established necrotizing fasciitis associated with monomicrobial pseudomonas infection in a 34 years old male. The patient presented with painful, necrosed areas of skin and soft tissue over right gluteal region which rapidly progressed to right upper back. Aggressive supportive measures and early debridement lead to a full recovery with no functional deficits.